Problems of ruminant reproduction in Malaysia. - Tan, H. S. (1983)
Reproductive efficiency is a major factor affecting livestock profitability. Sub-optimal reproductive performance of ruminants is a worldwide problem, especially in tropical countries. In view of current emphasis on cattle development, the nature and extent of reproductive problems in large ruminants are described. Sufficient data are available on reproductive performance of cattle and buffaloes (e.g. age at first calving, services per conception, non-return rate, calving interval) at farm level but more data related to fertility and infertility under small-holder conditions are required. Ruminant infertility usually results from a combination of climatic, genetic, management, nutritional and disease factors, leading either to fertilization failure or embryonic mortality. Reproductive problems reported include anestrus, repeated breeding, abortion, dystokia, retained placenta and endometritis. Anestrus and repeated breeding are major problems and diagnosis of these conditions should be given high priority. True anestrus, either post-calving or post-breeding, may be important in some farms where suckling and poor nutrition may be predisposing factors. Management deficiency at the smallholder level, especially for imported, more productive cattle, must be corrected. The national status of infectious reproductive disease needs further study. Although brucellosis and leptospirosis are endemic in certain farms, the prevalence and epidemiology of other diseases (e.g. vibriosis, IBR, mycoplasmosis) have to be evaluated further. Despite the success of A.I. in cattle breeding, certain constraints have affected the progress of this technology locally. The problems related to the application of A.I. under field conditions are discussed. The need for genetic improvement is great but until management, nutrition and A.I. services are improved especially at the smallholder level, the genetic impact of this technology will not be felt. With the heavy importation of cross-bred cattle, infertility problems are bound to increase in significance. Research on infertility, both at the farm and smallholder level, must be strengthened to meet the national objective of self-sufficiency in milk and meat. The ultimate goal is to lower calving intervals and the number of services per conception in order to maximise productivity from ruminant.